Influence of the Polish Language on the Semantics, Syntax and Pragmatics of Prepositions in the Speech of the Old Believers living in Poland - Яскульски, Адам (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]The main aim of this paper is to present the influence of the Polish language on the semantics, syntax and pragmatics of prepositions that are being used by Polish Old Believers. Nowadays, the Polish Old Believers live in a language island. Language islands are detached from their ethnolinguistic roots and suffer a constant shortage of language structures. On the one hand, they acquire the language of the dominant group; on the other hand, it is important for them to preserve the language of their ancestors. The Old Believers’ Russian dialect is and has been under the influence of the Polish language for over a century. The author presents prepositions that were observed in the speech of Old Believers living in Poland and are also typical for the Polish language. Thus, in all probability, they can be considered as a result of Polish influence in the Russian dialect.